2023
DOI: 10.3389/fmicb.2023.1117017
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing reveals high-risk clones of Pseudomonas aeruginosa in Guangdong, China

Abstract: The ever-increasing prevalence of infections produced by multidrug-resistant or extensively drug-resistant Pseudomonas aeruginosa is commonly linked to a limited number of aptly-named epidemical ‘high-risk clones’ that are widespread among and within hospitals worldwide. The emergence of new potential high-risk clone strains in hospitals highlights the need to better and further understand the underlying genetic mechanisms for their emergence and success. P. aeruginosa related high-risk clones have been sporad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The STs found in P. aeruginosa have been associated with hospital-acquired infections: ST285, ST274, ST1404, and ST228 have been identified in hospitals in several European countries. The other STs have been reported in hospitals in Brazil, China, the United States, and Saudi Arabia [ 68 ]. Interestingly, we found two new allelic combinations for HU5 and HU6 isolates.…”
Section: Resultsmentioning
confidence: 99%
“…The STs found in P. aeruginosa have been associated with hospital-acquired infections: ST285, ST274, ST1404, and ST228 have been identified in hospitals in several European countries. The other STs have been reported in hospitals in Brazil, China, the United States, and Saudi Arabia [ 68 ]. Interestingly, we found two new allelic combinations for HU5 and HU6 isolates.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown mutual exclusion of the exoU and exoS genes [ 33 , 34 ], and exoU -positive strains presented multiple resistance mechanisms and stronger virulence in G. mellonella [ 13 ]. The exoU and/or exoS genes were positive in XDR-hvPA, and two strains co-carried exoU and exoS genes simultaneously, which may increase drug resistance and virulence [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results were interpreted on the basis of SIR (S: Sensitive; I: Intermediate; R: Resistant) according to the Clinical and Laboratory Standards Institute (CLSI M100-S32) guidelines. MRSA was defined as S. aureus expressing the mecA gene and/or Phenocillin®, while MDRSA strains were classified as MRSA and any isolates resistant to at least three antimicrobial classes [ 13 ].…”
Section: Methodsmentioning
confidence: 99%